Physiological Responses of Typical Wetland Plants Following Flooding Process—From an Eco-Hydrological Model Perspective - Liu, Chengliang; Zeng, Yijian; Su, Zhongbo; Zhou, Demin (Frontiers in Ecology and Evolution, 2022)
Anaerobics increase resistance to gas transport and microbial activity in flooded soils. This may result in the presence of aerenchyma in the roots of some wetland plants. Increased aerenchyma airspaces enable oxygen to be transported from the above-ground plant parts to the submerged roots and rhizosphere. Nevertheless, there is still a lack of studies linking field experiments and eco-hydrological modelling to the parametrization of the physiological responses of typical wetland plant species to natural flooding events. Furthermore, from the modelling perspective, the contribution of aerenchyma was not sufficiently considered. The goal of this study was to develop and apply an eco-hydrological model capable of simulating various patterns of plant physiological responses to natural flooding events based on key processes of root oxygen diffusion and aerenchyma functioning in a variably-saturated wetland soil environment. Eco-hydrological experiments were conducted accordingly, with surface water level, root-zone soil water content, soil temperature, leaf net photosynthesis rate and root morphology monitored simultaneously in situ at a site dominated by meadow species Deyeuxia angustifolia (Kom.) Y. L. Chang and invaded shrub species Salix rosmarinifolia Linn. var. brachypoda (Trautv.et Mey.) Y.L.Chou in a typical natural floodplain wetland. The results are as follows: (1) Root oxygen respiration rates are strongly correlated with leaf net photosynthesis rates of the two plant types, particularly under flooding conditions during the growing season; (2) Meadow species with a preference for wet microhabitats has a competitive advantage over first-year invading shrub species during flooding events; and (3) an aerenchyma sub-model could improve the eco-hydrological model’s accuracy in capturing plant physiological responses. These findings have the potential to contribute to the management of wetland and its restorations.